Punk: Pengamen Jalanan dan Sebuah Subkultur Dari Kehidupan Urban di Kota Medan - Agung Suharyanto (Universitas Negeri Medan, 2021)
This article aims to describe street children Punk in the life patterns of the people of Medan City. Medan city is one of the things that cannot be separated from the life pattern of street singers. This means that the life of street singers has become part of the overall life of the people of Medan City. Don't know who started it, now there are so many Punk communities scattered at the crossroads, living in groups while busking. Their identity is very different from other street singers, both in terms of clothes, hairstyles and body piercing as well as tattoos on several parts of the body. All things that are very different from the identity of the other buskers whose taste is also piling up. What makes the other street singers the same is that their songs and music are no different, which are trending and melancholy. They also use the media of music to create space for themselves to speak out. Music is used as a tool to empower himself. Apart from looking for food, playing music is also a tool to build solidarity. On certain occasions they played music together. So, you could say, young people in Medan who are singing on the streets and wearing all-Punk make-up in Indonesia are very likely inspired by something very different from their predecessor Punk generation in their home country.